Vitamin D Receptor and Retinoid X Receptor Alpha in Melanocytic Benign Lesions and Melanoma - Ocanha Xavier, Juliana Polizel [UNESP]; Xavier, José Cândido Caldeira [UNESP]; Da Silva, Márcia Guimarães [UNESP]; Marques, Mariângela Esther Alencar [UNESP] (Wolters Kluwer, 2023)
Vitamin D receptor (VDR) exerts its biological effects when it heterodimerizes to a nuclear receptor of the retinoid family called retinoid X receptor α (RXRα), stimulating or inhibiting DNA transcription. VDR stimulation by vitamin D analogs led to in vitro antiproliferative effects, and experimental RXRα knockout led to loss of proliferation control in melanoma cells. The aim of this study was to determine VDR and RXRα positivity in melanocytic lesions, compared with normal skin species. By immunohistochemistry assays, nuclear VDR, cytoplasmic VDR, and RXRα and RXRα in keratinocytes surrounding melanocytes were evaluated in 77 controls, 92 intradermal nevi, 54 dysplastic nevi, and 83 melanomas in this retrospective cross-sectional study. Nuclear VDR, cytoplasmic VDR, and RXRα were less expressed in exposed areas (P < 0.001, P = 0.0006, and P < 0.001, respectively) than covered areas. All melanocytic lesions had loss of VDR and RXRα comparing with the control group. In the melanoma group, nuclear VDR tended to inversely correlate with the Breslow index (r = -0.11, P = 0.29) but directly correlated with histological regression (P = 0.0293). RXRα inversely correlated with mitosis (r = -0.245; P = 0.0263). We can suggest that sun exposure affected VDR and RXRα immunopositivity. Nuclear VDR tendency of inverse correlation with the Breslow index showed that worse melanomas have a greater loss of VDR. RXRα inversely correlated with mitosis, indicating that RXRα can have a role in proliferation control. VDR and RXRα may participate in the development of melanocytic lesions and be a future target of new studies and directed therapies.
Keywords: calcitriol; melanoma; nevus; retinoid X receptor alpha; VDR